2003
DOI: 10.1523/jneurosci.23-08-03364.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional NMDA Receptor Subtype 2B Is Expressed in Astrocytes after IschemiaIn Vivoand AnoxiaIn Vitro

Abstract: NMDA-type glutamate receptors play a critical role in neuronal synaptogenesis, plasticity, and excitotoxic death. Recent studies indicate that functional NMDA receptors are also expressed in certain glial populations in the normal brain. Using immunohistochemical methods, we detected the presence of the NMDA receptor 2B (NR2B) subunit of the NMDA receptor in neurons but not astrocytes in the CA1 and subicular regions of the rat hippocampus. However, after ischemia-induced neuronal death in these regions, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 67 publications
4
74
0
Order By: Relevance
“…The fact that we were not able to immunologically detect the NR1 subunit in these cells suggests that, at rest, astrocytes lack the capacity to express functional NMDAR channels or that NR1 levels are below detection. An intriguing possibility is that NR1 expression is upregulated in hippocampal astrocytes by ischemia or anoxia, as previously reported (Krebs et al, 2003). Consistent with the idea that functional NR2C-containing NMDARs may be expressed in response to ischemia, cerebral vascular occlusion selectively increases NR2C mRNA expression in vulnerable areas (Small et al, 1997) and mutation of the NR2C gene reduces ischemic injury in mice (Kadotani et al, 1996).…”
Section: Expression Of the Nr2c In Non-neuronal Cellssupporting
confidence: 77%
“…The fact that we were not able to immunologically detect the NR1 subunit in these cells suggests that, at rest, astrocytes lack the capacity to express functional NMDAR channels or that NR1 levels are below detection. An intriguing possibility is that NR1 expression is upregulated in hippocampal astrocytes by ischemia or anoxia, as previously reported (Krebs et al, 2003). Consistent with the idea that functional NR2C-containing NMDARs may be expressed in response to ischemia, cerebral vascular occlusion selectively increases NR2C mRNA expression in vulnerable areas (Small et al, 1997) and mutation of the NR2C gene reduces ischemic injury in mice (Kadotani et al, 1996).…”
Section: Expression Of the Nr2c In Non-neuronal Cellssupporting
confidence: 77%
“…NMDA receptors are known to be expressed in neurons (45), while astrocytes react to glutamate by metabotropic receptors and express NMDA subunits only under pathological conditions such as ischemia or anoxia (46). In contrast, recent studies have clearly demonstrated the presence of functional NMDA subunits in cortical astrocytes in the normal brain (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sections of these tissues were cut on a cryostat, thaw-mounted on Superfrost slides (VWR, Edmonton, Alta, Canada), fixed, and labelled as described above. Primary cultures of rat neurons were obtained from K. Baimbridge (Department of Physiology, University of British Columbia, Vancouver, BC, Canada) [19,20]. The neurons were fixed, and then labelled as described above.…”
Section: Animals Male Wistar Rats (200-235 G; University Of Britishmentioning
confidence: 99%